Effective communication in criminal justice - Grubb, Robert E.; Hemby, K. Virginia (Thousand Oaks, California SAGE Publications, Inc., 2019)
"Authors Robert E. Grubb and K. Virginia Hemby teach students how to be both effective writers and communicators--essential skills for anyone interested in criminal justice. Going beyond report writing, this book helps readers become more confident presenters and digital communicators while encouraging students to adapt their communication styles to meet the needs of diverse populations. Students will not only improve their communication and writing skills but also gain specific strategies for succeeding in careers related to policing, courts, corrections, and private security."--Back cover.
The basics of effective communication -- Communication : words are not enough -- Think before you speak : the verbal component -- Actions speak louder than words : nonverbal communication -- Preparing for effective communication -- Grammar : a lesson in the basics -- Preparing to speak : presentations and visual aids -- Effective communication in your professional sphere -- Written communication : an agency's lifeline -- Interviewing and interrogating: witnesses and suspects -- The court system : preparing for and testifying in court -- Technology and communication : a new frontier -- Conflict resolution and other special forms of communication -- Effective communication with different populations -- Communication with diverse populations : ethnic/cultural groups and children and youth -- Communication with special groups : cognitive, physiological, psychological, and emotional disabilities.
Includes bibliographical references and index.
Keywords: Communication in law enforcement; Criminal justice, Administration of; Criminal records -- Management